2010
DOI: 10.1177/104063871002200110
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Two Commercial Loop-Mediated Isothermal Amplification Assays for Detection of Avian Influenza H5 and H7 Hemagglutinin Genes

Abstract: Abstract. Real-time reverse transcription loop-mediated isothermal amplification (real-time RT-LAMP) holds substantial potential as a highly sensitive, specific, and easy-to-perform molecular technique for pathogen detection in clinical samples. In the current study, the analytical and diagnostic performance of 2 commercial realtime RT-LAMP kits, Avian Flu H5 and Avian Flu H7, in detecting Avian influenza virus (AIV) infections were evaluated and compared with validated real-time reverse transcription polymera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…In our study, both the RT-LAMP and qRT-PCR assays showed comparable sensitivity for the detection of DENV in patients’ sera (Îș = 0.939), even though the sensitivity of RT-LAMP was slightly lower than that of qRT-PCR. Similar findings have been reported in several other studies for the evaluation of LAMP assay when compared against the qPCR [46,47]. The RT-LAMP assay in this study gave possibly six false negative and one false positive results.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, both the RT-LAMP and qRT-PCR assays showed comparable sensitivity for the detection of DENV in patients’ sera (Îș = 0.939), even though the sensitivity of RT-LAMP was slightly lower than that of qRT-PCR. Similar findings have been reported in several other studies for the evaluation of LAMP assay when compared against the qPCR [46,47]. The RT-LAMP assay in this study gave possibly six false negative and one false positive results.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, a reverse transcription loop-mediated isothermal amplification (RT-LAMP) assay was developed for the detection of the AIV H5 gene (Imai et al, 2006(Imai et al, , 2007Jung et al, 2015;Liu et al, 2013;Postel et al, 2010). The H5 RT-RPA is faster than RT-LAMP (5-7 min in H5 RT-RPA compared to 30-60 min in real time RT-LAMP).…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, as less manipulation of samples is required, it has been suggested that the risks of accidental contamination can be significantly reduced [23]. However, one of the most important factors in optimizing these methods relies on the design of appropriate primers, a more complex procedure than that for conventional PCR [24,25], and 4) and conventional PCR, which is generally considered as the method of choice for the detection of viral DNA present at very low amounts in biological samples [4,26-31], but, just as the above mentioned methods, a number of important disadvantages have been reported by the use PCR for WSSV detection. Thus, the Office of International Epizootic (OIE) recommends, among few other molecular techniques, the use of a two-step nested PCR protocol described by [26,32] for all situations where WSSV diagnosis is required [33].…”
Section: Introductionmentioning
confidence: 99%